Phase behaviour of a simple fluid confined in a periodic porous material - Stopper, Daniel; Schroder-Turk, Gerd E.; Mecke, Klaus; Roth, Roland (Molecular Physics, 2021)
Using density functional theory for a simple fluid of hard spheres with a square-well attraction, we study the phase behaviour of the fluid confined in triply periodic porous material, where the pore space is bounded by a bicontinuous minimal surface. We combine our numerical results with the morphometric thermodynamics, an ansatz that expresses thermodynamic quantities as a linear combination of four additive geometrical terms, and analyse the dependency of the transition point between a liquid and a gas on the geometrical properties of the confining space. By demonstrating that the morphometric approach can be employed in order to account for the thermodynamic behaviour of a simple fluid in a complex porous material, we make the first step towards a better understanding of experimental observations that can help to characterise the pore space.
CRIS-Team WoS Importer:2021-04-02